Carry on caring: infected females maintain their parental care despite high mortality. (21st April 2021) - Ratz, Tom; Monteith, Katy M; Vale, Pedro F; Smiseth, Per T
Abstract: Parental care is a key component of an organism's reproductive strategy that is thought to trade-off with allocation toward immunity. Yet, it is unclear how caring parents respond to pathogens: do infected parents reduce care as a sickness behavior or simply from being ill or do they prioritize their offspring by maintaining high levels of care? To address this issue, we investigated the consequences of infection by the pathogen Serratia marcescens on mortality, time spent providing care, reproductive output, and expression of immune genes of female parents in the burying beetle Nicrophorus vespilloides . We compared untreated control females with infected females that were inoculated with live bacteria, immune-challenged females that were inoculated with heat-killed bacteria, and injured females that were injected with buffer. We found that infected and immune-challenged females changed their immune gene expression and that infected females suffered increased mortality. Nevertheless, infected and immune-challenged females maintained their normal level of care and reproductive output. There was thus no evidence that infection led to either a decrease or an increase in parental care or reproductive output. Our results show that parental care, which is generally highly flexible, can remain remarkably robust and consistent despite the elevated mortality caused by infection by pathogens. Overall, these findings suggest that infected females maintain a high level of parental care, a strategy that may ensure that offspring receive the necessary amount of care but that might be detrimental to the parents' own survival or that may even facilitate disease transmission to offspring. Abstract : Sick parents face the dilemma of whether to prioritize their own health and reduce care to their offspring or prioritize their offspring by maintaining high levels of care. We investigated this by infecting breeding females of burying beetles with a pathogen and found that infected females maintained normal levels of care despite suffering from increased mortality. Parents might thus seek to prioritize care to the offspring over their own health.